Odpowiedzi

2010-04-13T19:36:47+02:00
B) (a3=-9
(a15=-3

a1+2r=-9 => a1=-9-2r
a1+14r=-3

-9-2r+14r=-3
12r=6
r=0,5

a1=-8
odp
an=-7,5+0,5n

c) (a5=4
(a21=8

a1+4r=4 => a1=4-4r
a1+20r=8

4-4r+20r=8
16r=4
r=0,25

a1=3
odp
an=2,75+0,25n

1 1 1
  • Użytkownik Zadane
2010-04-13T19:36:48+02:00
TERAZ JEST DOBRZE, POPRZEDNIK W PUNKCIE B POPEŁNIŁ BŁĄD

b)
(a1+2r=-9
(a1+14r=-3
a1=-9-2r
-9-2r+14r=-3
12r=6
r=1/2
a1=-10
an=a1+(n-1)r
an=-10+1/2(n-1)

c)
(a1+4r=4
(a1+20r=8
a1=4-4r
4-4r+20r=8
16r=4
r=1/4
a1=3
an=3+1/4(n-1)

2 4 2